A Self‐Polymerized Nitro‐Substituted Conjugated Carbonyl Compound as High‐Performance Cathode for Lithium‐Organic Batteries. Issue 9 (30th January 2020) - Li, Qiang; Wang, Haidong; Wang, Heng‐guo; Si, Zhenjun; Li, Chunping; Bai, Jie
Abstract: Conjugated carbonyl compounds have received much attention as cathode materials for developing green lithium‐ion batteries (LIBs). However, their high dissolution and poor electronic conductivity in organic electrolyte restrict their further application. Herein, a self‐polymerized nitro‐substituted conjugated carbonyl compound (2, 7‐dinitropyrene‐4, 5, 9, 10‐tetraone, PT‐2 NO2 ) is applied as a high‐performance cathode material for LIBs. PT‐2 NO2 exhibits a high reversible capacity of 153.9 mAh g −1 at 50 mA g −1 after 120 cycles, which is higher than that of other substituted compounds. Detailed characterization and theoretical calculations have testified that PT‐2 NO2 is transformed into an azo polymer through an irreversible reductive coupling reaction in the first discharge process, and then carbonyl and azo groups reversibly react with Li ions in subsequent cycles. In addition, this azo polymer is also synthesized and applied as the electrode material, which shows similar electrochemical performance to PT‐2 NO2 but with higher initial coulombic efficiency. Thus, this work provides a simple but effectively way to construct organic cathode materials with multiple redox sites for green and high‐performance LIBs. Abstract : Do it yourself : A self‐polymerized nitro‐substituted conjugated carbonyl compound is synthesized, the nitro group of which can be electrochemically reduced into azo compounds that served as both linker and active site. When applied as a cathode material for lithium‐ion batteries (LIBs), both carbonyl and obtained azo groups can undergo reversible reactions with Li ions and deliver superior electrochemical performance.